First-line immune checkpoint inhibitors plus targeted therapy versus sorafenib or lenvatinib monotherapy for unresectable or advanced hepatocellular carcinoma: a meta-analysis of phase 3 trials - Lin, Yuxuan; Liao, Yonghe; Luo, Bo; Shen, Jinhai (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitor (ICI) and targeted therapy (TT) combinations have emerged as promising first-line treatments for unresectable or advanced hepatocellular carcinoma (u/aHCC), leveraging synergistic anti-tumor effects. However, the comparative efficacy and safety of ICI-TT regimens versus sorafenib or lenvatinib (S/L) monotherapy require further elucidation across larger patient populations. This meta-analysis synthesizes data from phase 3 trials to evaluate the clinical benefits and risks of first-line ICI-TT combination therapy in u/aHCC.MethodsWe conducted systematic searches in PubMed and major oncology conference proceedings up to June 10, 2025. Eligible studies were randomized phase 3 trials comparing first-line ICI-TT versus S/L monotherapy in u/aHCC. Efficacy outcomes included progression-free survival (PFS), overall survival (OS) (summarized as hazard ratios [HRs] with 95% confidence intervals [CIs]), and objective response rate (ORR) (evaluated using odds ratios [ORs]). Safety outcomes assessed grade 3–5 treatment-related adverse events (TRAEs) and serious TRAEs, reported as relative risks (RRs).ResultsEight phase 3 trials (IMbrave150, ORIENT-32, COSMIC-312, CARES-310, LEAP-002, SCT-I10A-C301, HEPATORCH, APOLLO) involving 4,379 patients were included. Compared with S/L monotherapy, ICI-TT combination therapy demonstrated significantly improved ORR (OR 3.93; 95% CI 2.64–5.85), PFS (HR 0.62; 95% CI 0.54–0.71), and OS (HR 0.71; 95% CI 0.62–0.82). The risk of grade 3–5 TRAEs was not significantly increased with combination therapy (RR 1.13; 95% CI 0.96–1.33). However, combination therapy was associated with a significantly higher risk of serious TRAEs (RR 1.97; 95% CI 1.50–2.60).ConclusionFirst-line ICI-plus-TT combination therapy demonstrates superior efficacy in ORR, PFS, and OS compared to S/L monotherapy for u/aHCC, without a significant increase in grade 3–5 TRAEs. Clinicians should be aware of the elevated risk of serious TRAEs associated with combination regimens. These findings support ICI-TT as a preferred first-line strategy for eligible patients, although individualized risk-benefit assessment remains crucial.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251053588.